CLINICAL EFFICACY AND TRANSFER OF BMY-28100 TO BLOOD AND SKIN - SHINOMIYA, SHIGERU; TODA, KIYOSHI; OHTA, MIDORI; SHONO, SHIGEAKI; OSAKU, AYA (CHEMOTHERAPY, 1989)
We performed basic and clinical studies on BMY-28100 in dermatological infections, with the following results. 1. Five-hundred mg of BMY-28100 was orally administered to 9 patients with benign skin tumors, and 2h later the blood level of the drug and its transfer to the skin were determined. The mean concentration of BMY-28100 was 9.16μg/ml in blood and 2.24μg/g in dermal tissue. 2. We carried out a clinical study on 12 patients with skin disease. The clinical efficacy rate was about 92%.